Enhancing Student’s Speaking Skills Through the use of Adjectives in Prsent Tense Non-Verbal Sentence to Grade 5 Students at SD Negeri 091608 Sinaksak - Sitepu, Dhea Natasya; Sembiring, Ribby Violin; Chandrawinata, Femy; Herman, Herman (AMK : Abdi Masyarakat UIKA, 2025)
This study aims to improve the speaking skills of fifth-grade students at SD Negeri 091608 Sinaksak through the implementation of the Grammar-Translation Method (GTM). The main problem faced by the students was their low ability to speak English, especially in constructing simple sentences and expressing them confidently. The subjects of the study were 19 fifth-grade students. The instruments used included observation sheets, speaking tests, and documentation of teaching activities. The results showed that the use of GTM helped students better understand sentence structure through simple translation exercises from Indonesian to English. This positively impacted their speaking abilities. In conclusion, the Grammar-Translation Method can be considered an effective alternative teaching strategy to enhance English speaking skills among elementary school students.